1999
DOI: 10.1046/j.1365-2672.1999.00841.x
|View full text |Cite
|
Sign up to set email alerts
|

Nisin, temperature and pH effects on growth and viability of Pectinatus frisingensis, a Gram-negative, strictly anaerobic beer-spoilage bacterium

Abstract: Pectinatus frisingensis, a Gram‐negative and strictly anaerobic beer spoilage bacterium is sensitive to nisin. An increase in nisin concentration (0 to 1100 IU ml−1) added to the culture medium prolonged the lag phase, and decreased the growth rate of the bacterium. In addition, late exponential cells of P. frisingensis exposed to low concentrations of nisin lost immediately a part of their intracellular K+. Presence of Mg2+ up to 15 mmol l−1 did not protect P. frisingensis from nisin‐induced loss of viability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
1
13
2
1
Order By: Relevance
“…This differs from previous findings where Pectinatus cerevisiiphilus was found to be highly sensitive to vancomycin (Helander et al, 1994) and Pectinatus frisingensis was shown to be sensitive to nisin (Chihib et al, 1999). FSRU B0405…”
Section: Strain Fsru B0405contrasting
confidence: 56%
“…This differs from previous findings where Pectinatus cerevisiiphilus was found to be highly sensitive to vancomycin (Helander et al, 1994) and Pectinatus frisingensis was shown to be sensitive to nisin (Chihib et al, 1999). FSRU B0405…”
Section: Strain Fsru B0405contrasting
confidence: 56%
“…This surprising result is explained by findings indicating that the outer membrane of Pectinatus does not form an effective barrier: the above study also demonstrated a high sensitivity of Pectinatus strains to vancomycin and bacitracin, which are rather large molecules (M r , 1449 and 1411, respectively) unable to penetrate a normal outer membrane in most bacteria (Vaara, 1993). Furthermore, P. frisingensis was shown to be sensitive to nisin, which is a cationic peptide acting lethally on the bacterial cytoplasmic membrane, but is unable to penetrate an intact outer membrane (Chihib et al, 1999b). Gram-negative bacteria are normally insensitive to nisin action (Helander et al, 1997).…”
Section: Physiological and Biochemical Properties Of Pectinatusmentioning
confidence: 75%
“…A number of studies on Pectinatus growth in the culture medium as a function of temperature, pH and ethanol concentration have been performed (Tholozan et al, 1996;Tholozan et al, 1997;Chihib and Tholozan, 1999a;Chihib et al, 1999b) including modeling of growth and metabolite production (Membré and Tholozan, 1994;Watier et al, 1996b). In general, the parameters derive from those encountered in beer production, including rapid temperature changes in pasteurization and cooling before bottling.…”
Section: Physiological and Biochemical Properties Of Pectinatusmentioning
confidence: 99%
“…Notably P. cerevisiiphilus has been shown to be susceptible to vancomycin and bacitracin 67 , which are large molecules that are normally unable to penetrate the outer membrane of Gram-negative bacteria. It has also been demonstrated that P. frisingensis is sensitive to nisin, a large antibacterial peptide that normally does not affect Gram-negative bacteria 27 . These results suggest that the outer membrane of Pectinatus, in the conditions tested, does not act as an effective permeability barrier.…”
mentioning
confidence: 99%